2021
DOI: 10.3390/cancers13194889
|View full text |Cite
|
Sign up to set email alerts
|

DJ4 Targets the Rho-Associated Protein Kinase Pathway and Attenuates Disease Progression in Preclinical Murine Models of Acute Myeloid Leukemia

Abstract: The poor prognosis of acute myeloid leukemia (AML) and the highly heterogenous nature of the disease motivates targeted gene therapeutic investigations. Rho-associated protein kinases (ROCKs) are crucial for various actin cytoskeletal changes, which have established malignant consequences in various cancers, yet are still not being successfully utilized clinically towards cancer treatment. This work establishes the therapeutic activity of ROCK inhibitor (5Z)-2–5-(1H-pyrrolo[2,3-b]pyridine-3-ylmethylene)-1,3-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…In our previously reported studies, we observed that DJ4 treatment exhibited minor effects on proliferation of A549 and MDA-MB-231 cells after 24 h of exposure [ 11 ]. Interestingly, we observed much more profound effects on cell viability in acute myeloid leukemia (AML) cell lines at 24 h [ 12 ]. To determine whether the effects on cell viability in AML cells were related to the specific cancer subtypes, or to differences in temporal response to DJ4, we examined whether DJ4 affected the viability of various NSCLC cells over longer periods of drug exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In our previously reported studies, we observed that DJ4 treatment exhibited minor effects on proliferation of A549 and MDA-MB-231 cells after 24 h of exposure [ 11 ]. Interestingly, we observed much more profound effects on cell viability in acute myeloid leukemia (AML) cell lines at 24 h [ 12 ]. To determine whether the effects on cell viability in AML cells were related to the specific cancer subtypes, or to differences in temporal response to DJ4, we examined whether DJ4 affected the viability of various NSCLC cells over longer periods of drug exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ROCK1 was identified as a crucial gene for leukemic bulk and stem/progenitor cells using large-scale RNAi screens in primary human AML cells ( Wermke et al, 2015 ). DJ4, a novel ROCK inhibitor, was demonstrated to suppress ROCK/MYPT1/MLC2 pathway and result in cell death of AML cells ( Golla et al, 2021 ). As these findings suggested that ROCK1 could be a potential therapeutic target for AML, evaluating the anti-leukemia effect of ROCK1 inhibitor in preclinical models might be of potential value.…”
Section: Introductionmentioning
confidence: 99%
“…Rho-associated kinase1 (ROCK1) is a classic serine/threonine protein kinase. ROCK1 can regulate downstream substrates such as muscle Globulin, adducin and protein kinases [3]. ROCK1 also can phosphorylate various substrates such as myosin light chain (MLC) phosphatase, LIM kinase, PTEN, insulin receptor substrate (IRS), ezrin/radixin/moesin (ERM) proteins, and JNK interacting protein (JIP-3) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%